Methane Fluxes from Alpine Wetlands of Zoige Plateau in Relation to Water Regime and Vegetation under Two Scales - Chen, Huai; Wu, Ning; Wang, Yanfen; Gao, Yongheng; Peng, Changhui (Water, Air, & Soil Pollution, 2011)
Methane fluxes in alpine ecosystems remain insufficiently studied, especially in terms of the magnitude, temporal, and spatial patterns. To quantify the mean methane emission of alpine ecosystems, methane fluxes were measured among six ecosystems and microsites within each ecosystem at Zoige National Wetland Reserve. The average methane emission from Zoige Plateau was 2.25 mg CH4 m(-2) h(-1), which fell into the range of methane emission rate reported by a number of studies in other alpine wetlands. Prevailing ecosystem types had important impacts on the methane flux on the landscape scale. In the wet ecosystems, the microsites had different methane emissions resulting from the differences in the depth of water table and associated vegetation characteristics. The identification of the microsites based on their vegetation characteristics thus allows upscaling of methane emissions in these ecosystems. However, in the dry ecosystems showing even methane uptake, the spatial variation in the methane fluxes was low and the vegetation has a poor predicative value for the methane fluxes. There, the soil porosity linked to the gas diffusion rate in soil would be the key factor explaining methane fluxes.